A Multi-Objective Optimization Model For Sustainable Supply Chain Network - Fadhillah, Nurul; Sawaluddin, Sawaluddin; Suwilo, Saib (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Sustainable supply chains provide a strategic approach to tackling global challenges associated with operational efficiency and the three dimensions of sustainability: economic, environmental, and social. This research develops a multi-objective optimization model that integrates all three elements into the supply chain network. This model encompasses objectives like profit maximization, carbon emission reduction, waste minimization, enhancement of worker welfare, and resource optimization. This model's constraints embody actual restrictions, encompassing production and distribution capacity, demand, emissions, and social welfare. This case study of Mega Motor Company demonstrates the practical use of the methodology. This model is assessed using synthetic data through the Mixed-Integer Linear Programming (MILP) approach to determine its efficacy in meeting sustainability objectives. The evaluation results indicate that this model can deliver balanced solutions to enhance long-term efficiency and sustainability. This model functions as a strategic decision-making instrument for firms aiming to thoroughly establish a sustainable supply chain system.